DYNAMICS OF INDICATORS OF COMPETITIVE READINESS OF ATHLETES OF HIGH QUALIFICATION OF ACADEMIC ROWING - Popova, I. A.; Melnik , E. V. (Modern Psychology, 2019)
The article presents the results of a study of the competitive preparedness of highly qualified athletes in cyclic sports using the example of rowing. The dynamics of the indicators of the energy potential and the level of stress background diagnosed by the method of gas discharge visualization (GDV), the level of anxiety and motivation in the pre-competitive training period is established. The established relationship between the mental and functional components of preparedness serves as the initial prerequisite for determining the integral indicator of competitive readiness, on the basis of which planning the volume and intensity of loads in cyclic sports can be carried out, and the stability of the implementation of preparedness in the competitive season can be predicted.
Keywords: rowing, activation, motivation, preparatory period, competitive readiness, anxiety